The Use of Whatsapp Application as A Learning Method at SMP IT Nurul Ilmi Jambi - Saefulloh, Ahmad (Borneo International Journal of Islamic Studies, 2019)
This article tries to see how far the effectiveness of WhatsApp as a social media application is used as a means of teachers in educating and improving the quality of learning. WhatsApp (WA) is a new breakthrough for educators to communicate to students and parents of students in providing information services related to school learning programs that are connected in a chat group. This article aims to see how teachers use WhatsApp as a learning communication tool. This research was conducted at SMP IT Nurul Ilmi Jambi having its address at Jl. Julius Usman RT.18 Pematang Sulur Village, Telanaipura Jambi City. This research is a qualitative descriptive study. Data collection by observation method, direct interview and documentation. Techniques used in data analysis are data display, data reduction and conclusion. The data validity technique uses source triangulation. The results showed that in order to support the learning activities of students at SMP Nurul Ilmi Jambi, the teacher made the Whatsaap application an educational application involving teachers, students and parents. The use of WA in learning activities serves as an educational tool, means of evaluation, means of connecting information, as well as a means of consulting services and establishing friendship. Teachers establish communication groups through WhatsApp between teachers and students, and teachers with parents. Obstacles in the field found that not all students and parents of students actively participate in the discussion.